[tex]\bf (\stackrel{x_1}{-10}~,~\stackrel{y_1}{-20})\qquad (\stackrel{x_2}{1}~,~\stackrel{y_2}{-9}) \\\\\\ \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{-9}-\stackrel{y1}{(-20)}}}{\underset{run} {\underset{x_2}{1}-\underset{x_1}{(-10)}}}\implies \cfrac{-9+20}{1+10}\implies \cfrac{11}{11}\implies 1[/tex]
[tex]\bf \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{(-20)}=\stackrel{m}{1}[x-\stackrel{x_1}{(-10)}] \\\\[-0.35em] ~\dotfill\\\\ ~\hfill y+20=(x+10)~\hfill[/tex]